A new species of Eidmanacris Chopard, 1956, with notes on its distribution in Brazilian caves (Phalangopsidae, Luzarinae) - Bolfarini, Marcio P. (Zootaxa, 2016)
The genus Eidmanacris comprises 19 species distributed through Brazil, Bolivia ad Paraguay. In Brazil, the genus has a broad distribution, but its occurrence in Brazilian caves is poorly known; the only species recorded is E. alboannulata for the cave “Gruta da Toca”, Itirapina municipality, São Paulo State. In this study I describe a species, E. lencionii Bolfarini, n. sp., with a discussion on its distribution in Brazilian caves, and its relation with the hypogean environment. The type material is deposited in the Museu de Zoologia da Universidade de São Paulo (MZSP) and the Laboratório de Estudos Subterrâneos da Universidade Federal de São Carlos (LES/UFSCar).